Die Orationes Homeri des Leonardo Bruni Aretino : kritische Edition der lateinischen und kastilianischen Übersetzung mit Prolegomena und Kommentar - Thiermann, Peter. (Mnemosyne, Supplements, 1993)
Leonardo Bruni Aretino ( c. 1370-1444) was one of the most gifted and prolific translators of Greek authors in the early Italian Renaissance and a bestseller whose works often circulated in more than a hundred manuscripts. Moreover, Homer ranks as the most admired Greek poet in the Renaissance. The 'Orationes Homeri', id est Bruni's translation of three speeches from the embassy scene, are of focal interest in the studies of Renaissance literature in its many aspects: survival of ancient authors and their influence on Renaissance literature and literary theory, translation theory and practice, knowledge of Greek poetic language. This first critical edition with an introduction and a systematic commentary presents the 'Orationes Homeri' in comparison with other works of Bruni and translations of Homer by other humanists. It includes the part of the Lorenzo Valla version corresponding to the 'Orationes Homeri' and the Castilian version of the 'Orationes Homeri', which is the first vernacular translation of Homer.